2017
DOI: 10.1021/acs.biochem.7b00457
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heme Orientational Disorder in a Myoglobin Reconstituted with a Trifluoromethyl-Group-Substituted Heme Cofactor

Abstract: The orientation of a CF-substituted heme in sperm whale myoglobin and L29F, H64L, L29F/H64Q, and H64Q variant proteins has been investigated using F NMR spectroscopy to elucidate structural factors responsible for the thermodynamic stability of the heme orientational disorder, i.e., the presence of two heme orientations differing by a 180° rotation about the 5-15 meso axis, with respect to the protein moiety. Crystal structure of the met-aquo form of the wild-type myoglobin reconstituted with 13,17-bis(2-carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…This requires binding of substrates at relatively unique conformations. However, it has been shown that ligand binding to proteins might involve some level of heterogeneity ( 28 ). Enzymes with several substrates, like AK, bind them while in an open conformation and form the proper configuration of the active site only after binding ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…This requires binding of substrates at relatively unique conformations. However, it has been shown that ligand binding to proteins might involve some level of heterogeneity ( 28 ). Enzymes with several substrates, like AK, bind them while in an open conformation and form the proper configuration of the active site only after binding ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…[6,7,12,[50][51][52][53] Other studies on Mb reconstituted with artificially modified hemins supported the idea that the contacts of the peripheral substituents, especially the vinyl groups, with the residues of the heme pocket are much more important in determining the preferential heme orientation than the propionate-protein salt bridges. [54] More recently, the crucial role of steric interactions between the residue side chains and the heme peripheral groups in heme binding was identified, [55,56] favoring the intramolecular reorientation mechanism within the Mb heme crevice over the intermolecular mechanism. [56,57]…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%
“…Usually, the amount of reversed heme detected is quite small and its presence depends not only on the specific globin, but also on the oxidation and ligation states of the heme iron. The nature of the ligands has also been shown to be important [ 1–3,6–8,13–20 ] and the reversed heme orientation can affect the activity or the functional properties of the proteins. [ 21–25 ] For example, it was reported that the two conformer populations of native oxidized myoglobin (Mb) unfold and refold following two parallel kinetic reactions with rate constants differing 10‐fold, despite having identical absorption spectra and equilibrium thermodynamic stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Often, at least in the first phases found on cooling below the melting point, the disorder is dynamic, with the molecules or molecular ions undergoing rotational motion across a continuous distribution of molecular orientations, or jump rotations between a well-defined set of distinct orientations. Examples range from molecular crystals [1] such as fullerenes [2] to polyatomic ions in metal-organic frameworks [3] and even hemes in proteins [4]. Orientational disorder may lead to anomalous materials properties, such as reversible amorphisation under pressure [5] and giant barocaloric effects [6].…”
Section: Orientationally Disordered Crystalsmentioning
confidence: 99%